Self-Efficacy and Professional Identity Among Freshmen Nursing Students: A Latent Profile and Moderated Mediation Analysis - Mei, Xiao Xiao; Wang, Hui Yuan; Wu, Xiao Na; Wu, Jie Yi; Lu, Ying Zi; Ye, Zeng Jie (Frontiers in Psychology, 2022)
The major objective of this study was to identify the factors impacting freshmen nursing students’ professional identity, including the mediating effect of resilience and the moderation effect of role model. A descriptive correlational study was conducted from September to November 2020 at four universities in China, and 1051 freshmen nursing students (FNSs) from Be Resilient to Nursing Career (BRNC) program were recruited through convenience sampling. Results indicated that a four-class model based on self-efficacy was identified, including Lowest (15.6%), Med-low (45.0%), Med-high (32.7%) and Highest (6.7%) groups. Moreover, resilience played a pivotal role by partially mediating the relationship between self-efficacy and professional identity in FNSs and role model moderated the associations of resilience with professional identity. Therefore, integrated methods for assessing self-efficacy, resilience, whether haviong nursing role model or not and professional identity in FNSs are needed for nursing educators and clinical professionals. Implementing appropriate strategies to enhance resilience for FNSs with low self-efficacy and increase opportunities for freshmen nursing students to communicate with nursing role models in order to strengthen their professional identity is paramount.